Attitudes and Usage of the Food and Drug Administration Adverse Event Reporting System Among Gastroenterology Nurse Practitioners and Physician Assistants. (January 2016) - Salk, Allison; Ehrenpreis, Eli D.
Abstract : The Food and Drug Administration Adverse Event Reporting System (FAERS) is used for postmarketing pharmacovigilance. Our study sought to assess attitudes and usage of the FAERS among gastroenterology nurse practitioners (NPs) and physician assistants (PAs). A survey was administered at the August 2012 Principles of Gastroenterology for the Nurse Practitioner and Physician Assistant course, held in Chicago, IL. Of the 128 respondents, 123 (96%) reported a specialty in gastroenterology or hepatology and were included in analysis. Eighty-nine participants were NPs and 32 PAs, whereas 2 did not report their profession. Although 119 (98%) agreed or strongly agreed with the statement that accurately reporting adverse drug reactions is an important process to optimize patient safety, the majority of participants (54% NPs and 81% PAs) were unfamiliar with the FAERS. In addition, only 20% of NPs and 9% of PAs reported learning about the FAERS in NP or PA schooling. Our study shows enthusiasm among gastroenterology NPs and PAs for the reporting of adverse drug reactions, coupled with a lack of familiarity with the FAERS. This presents an opportunity for enhanced education about reporting of adverse drug reactions for gastroenterology NPs and PAs. Abstract : Supplemental Digital Content is Available in the Text.